Sports injuries in paralympic track and field athletes with visual impairment - Silva, M. P. M. E.; Winckler, C.; Silva, A. A. C. E.; Bilzon, J.; Duarte, E. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The aims of this study were to determine the epidemiology, nature, and pattern of sports injuries in Brazilian Paralympic track and field athletes with visual impairment and to assess differences between visual classes and sex.